2018
DOI: 10.1021/acs.iecr.8b00016
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Cu Bimetallic Catalysts for Selective CO2 Hydrogenation to Olefin-Rich C2+ Hydrocarbons

Abstract: This paper reports on Fe–Cu bimetallic catalysts supported on γ-alumina for selective CO2 hydrogenation to olefin-rich C2 + hydrocarbons. A strong synergetic promoting effect on C2 + hydrocarbon synthesis was observed over Fe–Cu bimetallic catalysts when the Cu/(Cu + Fe) atomic ratio was 0.17. Compared to monometallic Fe catalyst, the Fe–Cu bimetallic catalyst significantly enhances C2–C7 hydrocarbon formation and suppresses the formation of undesired CH4. The addition of K into Fe–Cu bimetallic catalysts inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 45 publications
3
54
0
Order By: Relevance
“…[33] Thus,a dding coppere nhances CO 2 conversion while keeping the product distribution constant. [57] This bimetallic catalysts upported on Al 2 O 3 reachedt he highest CO 2 conversion among all tested ratios. The addition of 10 % Cu to aF e ÀK/Al 2 O 3 catalysti ncreased CO 2 conversion to 41 %, relative to the unpromoted catalyst (24 %ofCO 2 conversion).…”
Section: Iron-basedcatalystsmentioning
confidence: 75%
See 4 more Smart Citations
“…[33] Thus,a dding coppere nhances CO 2 conversion while keeping the product distribution constant. [57] This bimetallic catalysts upported on Al 2 O 3 reachedt he highest CO 2 conversion among all tested ratios. The addition of 10 % Cu to aF e ÀK/Al 2 O 3 catalysti ncreased CO 2 conversion to 41 %, relative to the unpromoted catalyst (24 %ofCO 2 conversion).…”
Section: Iron-basedcatalystsmentioning
confidence: 75%
“…Higher Cu loadings showedl ower CO 2 conversion.W ang et al found that the optimal Cu/(Cu + Fe) atomic ratio was0 .17, whichc orresponded to 17 %t otal metal loading. [57] This bimetallic catalysts upported on Al 2 O 3 reachedt he highest CO 2 conversion among all tested ratios. Its XRD pattern showed an ew peak at 458,w hich was ascribed to FeÀCu alloy species.…”
Section: Iron-basedcatalystsmentioning
confidence: 75%
See 3 more Smart Citations